On the free bosonic string field theory for D≠26 - Aratyn, H.; Zimerman, A. H. (My University, 1986)
The free bosonic string field action is constructed for D≠26 which is invariant under off-mass-shell gauge transformations generalizing the standard BRS symmetry for D=26. Reduction of this model upon the gauge fixing procedure is analysed and an obstacle in imposing Virasoro gauge conditions is identified with the appearance of extra degrees of freedom. © 1986.